An innovative dynamic model for an integrated solar combined cycle power plant under off-design conditions. (15th September 2020) - Abdelhafidi, Nedjma; Yılmaz, İbrahim Halil and Bachari, Nour El Islam
Graphical abstract: Highlights: An innovative model for Integrated Solar Combined Cycle power plants is presented. Dynamic behavior of an Integrated Solar Combined Cycle is simulated under off-design. A new correlation has been introduced for the collector heat removal factor. The proposed model would provide better solar integration and control strategies. Abstract: The integrated solar combined cycle power plants are currently the most efficient way of converting solar energy into electricity. Increasing the thermal efficiency of these plants depends strongly on the dynamic characteristics of off-design conditions and the operational control strategies. An innovative mathematical model has been presented to investigate the dynamic behavior of an Integrated Solar Combined Cycle power plant in Hassi R'mel, Algeria under off-design conditions in this study. The proposed model is analyzed via computer simulation on the Matlab environment using the recent operating parameters of the plant and the meteorological data recorded by the Abener hybrid solar-gas central of Hassi R'mel. The simulation results indicate that the experimental data of the outlet temperature of the solar field and the power generated by the plant verify the predictions found by the model. The root mean square error and mean absolute error range respectively between 4.03 and 4.12 °C and 1.45–1.80 °C for the outlet temperature of the solar cycle and 1.61–1.72 MW and 0.67–0.75 MW for the net power under specified experimental conditions. It is revealed that the off-design conditions, particularly the direct normal irradiance and the wind speed, affect the Integrated Solar Combined Cycle performance significantly. The presented model is an effective tool that can provide a wealth of information to power plant operators and designers during operational plant design, and management to mitigate the adverse impact of possible off-design conditions on power production and to boost power production by management strategies.